Interpretation of sensor data from in situ tests on a transversely bonded fibre-reinforced polymer road bridge. (July 2019) - Sebastian, Wendel Michael; Johnson, Mike
The Frampton Cotterell fibre-reinforced polymer road bridge deck comprises pultruded glass-fibre-reinforced polymer units which are laid longitudinally and are adhesively bonded transversely, in contrast to previous glass-fibre-reinforced polymer deck bridges where the pultruded units were laid transversely. This novel layout dictates that transverse distribution of live loading occurs only through the deck's flanges and entails possible transverse tension which should be controlled to avoid cracks through the bonded deck–deck joints. This article assesses these structural actions by interpreting strains and deflections recorded during lorry testing of the bridge. Transverse distribution is evaluated by comparing transverse profiles of recorded longitudinal strains and of predicted longitudinal moments, with the conclusions qualitatively reinforced using a deflected surface based on the test recordings. Evidence of the deck acting as a continuum free of propagating joint cracks comes from the fact that the strains recorded during complementary lorry runs along the bridge satisfy the superposition principle and that the recorded strain influence lines replicate an idiosyncratic feature of the moment influence line without redistribution effects. That feature was then exploited to inform the strategy for a braking test which produced valuable vibration data for the bridge. Test data integrity is corroborated by cross checking deflections recorded from different types of sensors. It is concluded that since longitudinal placement of pultruded decks enhances the versatility of fibre-reinforced polymer bridges, this sensor layout and data interpretation process may form part of a wider strategy for health monitoring of such bridges.